Phospholipase C: underrated players in microbial infections - Singh, Vinayak; Rai, Rupal; Mathew, Bijina J.; Chourasia, Rashmi; Singh, Anirudh K.; Kumar, Awanish; Chaurasiya, Shivendra K. (Frontiers in Cellular and Infection Microbiology, 2023)
During bacterial infections, one or more virulence factors are required to support the survival, growth, and colonization of the pathogen within the host, leading to the symptomatic characteristic of the disease. The outcome of bacterial infections is determined by several factors from both host as well as pathogen origin. Proteins and enzymes involved in cellular signaling are important players in determining the outcome of host–pathogen interactions. phospholipase C (PLCs) participate in cellular signaling and regulation by virtue of their ability to hydrolyze membrane phospholipids into di-acyl-glycerol (DAG) and inositol triphosphate (IP3), which further causes the activation of other signaling pathways involved in various processes, including immune response. A total of 13 PLC isoforms are known so far, differing in their structure, regulation, and tissue-specific distribution. Different PLC isoforms have been implicated in various diseases, including cancer and infectious diseases; however, their roles in infectious diseases are not clearly understood. Many studies have suggested the prominent roles of both host and pathogen-derived PLCs during infections. PLCs have also been shown to contribute towards disease pathogenesis and the onset of disease symptoms. In this review, we have discussed the contribution of PLCs as a determinant of the outcome of host-pathogen interaction and pathogenesis during bacterial infections of human importance.